Numerical solution for a curvilinear crack phenomenon in thermoelectric bonded materials subjected to mechanical loadings - Mohd Nordin, Muhammad Haziq Iqmal; Hamzah, Khairum; Nik Long, Nik Mohd Asri; Khashi’ie, Najiyah Safwa; Waini, Iskandar; Zainal, Nurul Amira; Sayed Nordin, Sayed Kushairi (MDPI, 2024)
In this study, a curvilinear crack phenomenon laying in the upper part of thermoelectric bonded materials subject to mechanical loadings is considered. A curvilinear crack problem in thermoelectric bonded materials subjected to shear stress is formulated. The modified complex potential (MCP) function method is used to formulate this crack phenomenon into the hypersingular integral equations (HSIEs) with the help of the continuity conditions of the resultant electric force and displacement electric function. The normal and tangential traction along the crack segment serves as the right-hand side of the integral equation. The HSIEs are solved numerically for the unknown crack opening displacement (COD) function, electric current density, and energy flux load using the appropriate quadrature formulas. The numerical solution presented the behavior of the dimensionless stress intensity factors (SIFs) at the crack tips which depend on the elastic constant’s ratio, the position of the crack, the electric conductivity, and the thermal expansion coefficients.